Hubungan Nilai Budaya dan Dukungan Sosial Ibu dengan Pola Pemberian Makanan Tambahan di Kelurahan Wringinjajar Kabupaten Demak - Ananda Rahma Khoirun Nisa; Nopi Nur Khasanah; Kurnia Wijayanti (Journal of Health, Medical, and Psychological Studies, 2026)
Supplementary feeding (SF) plays an important role in improving the nutritional status of children and vulnerable groups. The success of the supplementary feeding program is influenced not only by medical factors but also by cultural values and maternal social support. This study aimed to analyze the relationship between cultural values and maternal social support with supplementary feeding practices in Wringinjajar Village, Demak Regency. This study employed a quantitative method with a cross-sectional design. A total of 142 respondents were included using a total sampling technique. Data were collected through questionnaires and analyzed using Spearman’s rho test. The results showed a moderate relationship between cultural values and supplementary feeding practices (ρ < 0.05) and a weak relationship between maternal social support and supplementary feeding practices (ρ < 0.05). In conclusion, positive cultural values and adequate maternal social support are associated with more appropriate supplementary feeding practices for children.